"Question 3 Simplify. (i) (x^2 − 5) (x + 5) + 25 (ii) (a^2 + 5) (b^3 + 3) + 5 (iii) (t + s^2) (t^2 − s) (iv) (a + b) (c − d) + (a − b) (c + d) + 2 (ac + bd) (v) (x + y) (2x + y) + (x + 2y) (x − y) (vi) (x + y) (x^2 − xy + y^2) (vii) (1.5x − 4y) (1.5x + 4y + 3) − 4.5x + 12y (viii) (a + b + c) (a + b − c)
Class 8 Algebraic Expressions and Identities Page 148"
Answers
Algebraic expressions:
A combination of constants and variables connected by any or all of the four fundamental operations +, -,×,÷ is called an algebraic expression
Multiplication of algebraic expression:
The product of two factors with like signs is positive and the product of two factors with unlike signs is negative.
Multiplication of a binomial and the binomial:
Let ( a+b)& (c+d) are two Binomials. By using distributive law of multiplatinum over addition twice, we may find their product
( a+b)× (c+d)
= a(c+d) + b( c+d)
=(a × c+a × d)+(b × c+b × d)
= ac+ad+bc+bd
This method is known as the horizontal method.
=========================================================
Solution:
i) (x²-5)(x+5)+25
x²(x+5) -5(x+5)+25
x³+ 5x² - 5x - 25 + 25
= x³ + 5x² -5x
ii) (a²+5)(b³+3)+5
a²(b³+3) +5(b³+3)
a²b³ + 3a² + 5b³ + 15 + 5
= a²b³ + 5b³ + 3a² + 20
iii) (t+s²)(t²-s)
t(t²-s)+ s²(t²-s)
t³-ts+s²t²-s³
iv) (a+b)(c-d)+(a-b)(c+d)+2(ac+bd)
a(c-d)+b(c-d) + a(c+d)-b(c+d) +2(ac+bd)
(ac - ad + bc - bd) + (ac + ad - bc - bd) + (2ac + 2bd)
= ac - ad + bc - bd + ac + ad - bc - bd + 2ac + 2bd
= ac+ac+2ac -ad+ad+bc-bc-bd-bd+2bd
= 4ac
v) (x + y) (2x + y) + (x + 2y) (x − y)
= x(2x + y)+y(2x + y) + x(x-y)+2y(x-y)
=2x² + xy + 2xy + y² + x² - xy + 2xy - 2y²
= 2x²+x²+xy-xy+2xy+2xy+y²-2y²
= 3x² + 4xy - y²
vi) (x + y) (x² − xy + y²)
x(x² − xy + y²) +y(x² -xy+y²)
= x³- x²y + xy² + x²y – xy² +y³
= x³ -x²y+x²y+xy²-xy²+y³
= x³ + y³
vi) (1.5x − 4y) (1.5x + 4y + 3) − 4.5x + 12y
= 1.5x(1.5x + 4y + 3) -4y(1.5x + 4y + 3) -4.5x+12y
=2.25x² + 6xy + 4.5x - 6xy - 16y² - 12y - 4.5x + 12y
= 2.25x² +6xy- 6xy+4.5x-4.5x-12y+12y-16y²
= 2.25x² - 16y²
vii) (a + b + c) (a + b − c)
= a(a + b − c)+b(a + b − c)+c(a + b − c)
= a² + ab - ac + ab + b² - bc + ac + bc - c²
= a² +ab +ab -ac+ac + b²- c² + bc-bc
= a²+2ab+b² - c²
=========================================================
Hope this will help you....